2018
DOI: 10.1186/s12944-018-0818-1
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Chymostatin and Aliskiren attenuates ER stress induced by lipid overload in kidney tubular cells

Abstract: BackgroundLipotoxicity plays an important role in the pathogenesis of kidney injury. Our previous study demonstrated that activation of local renin-angiotensin system (RAS) was involved in saturated free fatty acids palmitic acid (PA)-induced tubular cell injuries. The current study aims to investigate whether suppression of RAS by combination of direct renin inhibitor aliskiren and noncanonical RAS pathway chymase inhibitor chymostatin attenuates PA or cholesterol induced-endoplasmic reticulum stress (ER stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…How does PA induce autophagy and ER stress? Our previous studies showed that angiotensin-II plays a role in mediating in PA-induced ER stress and apoptosis in tubular cells 4 , suggesting a role of local RAS. Ang (1–7) and its G-protein coupled receptor Mas has been shown to counteract the classical RAS, conferring beneficial effects 5 , 6 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…How does PA induce autophagy and ER stress? Our previous studies showed that angiotensin-II plays a role in mediating in PA-induced ER stress and apoptosis in tubular cells 4 , suggesting a role of local RAS. Ang (1–7) and its G-protein coupled receptor Mas has been shown to counteract the classical RAS, conferring beneficial effects 5 , 6 .…”
Section: Discussionmentioning
confidence: 95%
“…Each RAS component has been identified in the kidney, suggesting the role of the local/tissue and intracellular RAS in the development and progression of renal diseases. We have recently demonstrated that blockade of RAS with direct renin inhibitor aliskiren, angiotensin-II type 1 receptor blocker valsartan, or chymase inhibitor chymostatin effectively attenuated tubular epithelial cell injuries induced by saturated fatty acid palmitic acid (PA) or high-fat diet (HFD) in mice 3 , 4 . As an alternative pathway of the RAS, angiotensin 1–7 (Ang (1–7)) and its G-protein coupled receptor Mas 5 , 6 (encoded by Mas1 gene, also named as Mrgprs 7 , the term “Mas” was used in the present article) has been extensively examined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, apoptosis is a physiological process of cell death and has been confirmed to be involved in the pathological process of SZ. Pro-apoptotic stimulation such as inflammation, autoimmunity, and oxidative stress may lead to the accumulation of reactive oxygen species (ROS) in mitochondria, affect the oxidative metabolic process, and then trigger the apoptosis of neurons and glial cells (6)(7)(8). Early studies have shown that 20-80% of neurons in the central nervous system die from apoptosis (9) and have reported the aberration of apoptotic regulatory proteins and DNA fragmentation status in the posterior temporal cortex (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, apoptosis is a physiological process of cell death and has been confirmed to be involved in the pathological process of schizophrenia. Pro-apoptotic stimulation such as inflammation, autoimmune and oxidative stress may lead to the accumulation of ROS in mitochondria, affect the oxidative metabolic process, and then trigger the apoptosis of nerve cells and glial cells [11][12][13]. Early studies have shown that 20-80% of nerve cells in the central nervous system die from apoptosis [14] and reported the aberration of apoptosis regulatory protein and DNA fragmentation status in the posterior temporal cortex [15,16].…”
Section: Introductionmentioning
confidence: 99%